CHEMICAL ALTERATION AND SUSCEPTIBILITY TEST OF SOME TOMATO CULTIVARS INFECTED WITH ROOT-KNOT DISEASE (Mesopotamia Journal of Agriculture)
The results showed increase in activity of the enzymes peroxidase , polyphenol oxidase and the total content of phenol in tomato cultivars infected with Meloidogyne javanica Raba'a cv. recorded significant superiority on the activity of peroxidase enzyme reached 0.74 Unit/g.fresh weight and total phenol content reached 6.69 mg/g. fresh weight compared with other cultivars. While it didn't differ significantly from Ward acv. In polyphenol oxidase activity reached 0.85 and 0.81 Unit/g. fresh weight in both cvs. respectively, This was reflected on number of gall/plant ,number of female/gram root and egg mass / gram root . It was noted that their values decreased with increasing of activity of peroxidase , polyphenoloxidase enzymes and total phenol content as observed in Raba'a cultivars which gave the lowest values reaching 15.3 , 18.6 and 5 for the same characters respectively.